(untitled) (Latakia University Journal -Biological Sciences Series, 2016)
يهدف هذا البحث إلى دراسة القدرة التراكمية لنباتي الأوكاليبتوس المنقاري( Eucalyptus camaldulensis) و العفص الشرقي (Biota orientalis) المزروعة في أرصفة شارع الشاطئ الأزرق في مدينة اللاذقية لعنصري الرصاص (Pb) والنحاس (Cu). جمعت العينات النباتية من الأوراق, القلف والخشب للأنواع المدروسة بالإضافة إلى عينات من التربة المحيطة بها وعلى عمق cm(0-20)، وتم تقدير تراكيز العناصر المدروسة باستخدام جهاز التحليل الطيفي بالامتصاص الذري (atomic absorption). بينت النتائج أن تراكيز Pb في الأنواع النباتية للأجزاء النباتية المدروسة تراوحت بين ppm)5.3-3.66) للأوكاليبتوس المنقاري و (ppm 2.8-10.29) للعفص الشرقي, بينما تراوحت كميات Cu بين (ppm 109.50-40.93) للأوكاليبتوس المنقاري و (ppm 63.36- 25.22) للعفص الشرقي. كما بينت نتائج هذا البحث قدرة القلف على مراكمة الرصاص أكثر من باقي الأجزاء النباتية, في حين أبدت الأوراق قدرة عالية على مراكمة عنصر النحاس حيث كان معامل التراكم الحيوي (BF>1), ويمكن اعتبار كلا النوعين مراكما جيدا لعنصر النحاس. This study aimed to study the accumulative abilities(Eucalyptus camaldulensis) and (Biota orientalis), planted in sidewalks of Al Shateaa street in Lattakia city regarding lead and copper. The plants samples of leaves, bark, wood were collected. And The soil samples were taken at 0-20 cm. Then the samples were analyzed by atomic absorption spectrophotometer. Results showed that the accumulated amounts of lead in different parts of E.camaldulensis and B.orientalis ranged between (3.66- 5.3ppm),(2.8-10.29 ppm) respectively. And the accumulated amounts of copper in different parts of E.camaldulensis and B.orientalis ranged between (109.50-40.93 ppm), (63.36- 25.22 ppm) respectivly. It was revealed that bark of Eucalyptus and Biota accumulated Pb more than the other parts, while E.camaldulensis and B.orientalis showed a hyper capacity to accumulate Copper element specially in its leaves where the the values of bioaccumulation factor (BF>1), that makes them as good Bioaccumulators to this element.